JEANNE KRAMER-SMYTH, ed., Partners for Preservation: Advancing Digital Preservation through Cross-Community Collaboration - Hurley, Grant (Archivaria, 2020)
Partners for Preservation: Advancing Digital Preservation through Cross-Community Collaboration. Jeanne Kramer-Smyth, ed. London: Facet Publishing, 2019. xxviii, 212 pp. ISBN 978-1-78330- 347-2